2008
DOI: 10.1017/s0022215108001904
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicine by patients attending a head and neck oncology clinic

Abstract: All medical practitioners should be aware of increasing complementary and alternative medicine usage by the United Kingdom population, and should be able to counsel patients appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
2
17
0
1
Order By: Relevance
“…Rees et al 110 reported a difference of 10% in the prevalence of CAM use when the recall period spanned 12 months (22%) compared with when the recall related to the time period since the cancer was diagnosed (32%), which spanned a mean of 4.4 years. Shakeel et al 117 found a difference of 24% in the prevalence rates of CAM use when the recall period spanned 12 months (26%) compared with when the recall related to the lifetime period (50%).…”
Section: Quantitative Data Analysismentioning
confidence: 99%
“…Rees et al 110 reported a difference of 10% in the prevalence of CAM use when the recall period spanned 12 months (22%) compared with when the recall related to the time period since the cancer was diagnosed (32%), which spanned a mean of 4.4 years. Shakeel et al 117 found a difference of 24% in the prevalence rates of CAM use when the recall period spanned 12 months (26%) compared with when the recall related to the lifetime period (50%).…”
Section: Quantitative Data Analysismentioning
confidence: 99%
“…Surveys carried out in the UK showed that 40.6% of cancer patients were using it. [ 53 54 55 56 57 58 ] A US survey revealed that 11% of cancer patients may be using aromatherapy. [ 59 60 ] The review concludes that use of diluted essential oils has minimal risks.…”
Section: Non Pharmacological Therapies In Cancer Pain Managementmentioning
confidence: 99%
“…5 However, a recent questionnaire survey conducted in UK head and neck cancer patients showed a prevalence of 50 per cent. 6 In head and neck cancers, both the disease and its treatment may be disfiguring, and basic swallowing, speech and respiration function can be affected. Patients may thus turn to complementary and alternative medicine.…”
Section: Introductionmentioning
confidence: 99%